LINKS BETWEEN FERTILITY, HAPPINESS AND GENDER ROLES - Galdauskaitė, Dovilė (Socialinė teorija, empirija, politika ir praktika, 2018)
The aim of this article is to present new theoretical approaches of fertility that explain links between childbearing, happiness and gender roles, gender (in)equality and gender (in)equity in a discussable way and highlight the prospectiveness of those approaches. A decline in fertility and low fertility rates are the negative fertility changes over the last few decades that were interpreted using the theory of second demographic transition (SDT) since the 1990s. However, rising fertility, which is observed in some countries, can’t be explained using SDT or rational choice theories of low fertility that are not complex enough. As a result of inconsistent fertility trends and the limitations of already developed theories, new theoretical perspectives are currently being developed. A theory suggested by Billari (2009), which links happiness and fertility, suggests the idea that there is positive relation between happiness and fertility, but it depends on micro- and macrolevel factors including the basic happiness level, personal knowledge and experience, objective well-being and various contextual conditions – political, social, institutional and cultural. This theoretical perspective considers changing gender role models as the most important contextual factors. Two separately emerging theories of commonalities between happiness and fertility as well as the changing gender roles framework are interrelated. That is why it is useful to connect ideas on happiness and gender dimensions to a single fertility theory. The main idea of this theoretical perspective is the discrepancy between women’s new gender role preferences and aspirations, when the family- and/or individual-oriented institutions do not suit the new emerging preferences, which, in turn, decreases happiness and fertility. This theoretical perspective complements SDT ideas suggested by R. Lesthaeghe, D. van de Kaa and P. McDonald’s ideas about gender equality, gender equity and the changing fertility level. The changes of gender role models, happiness and fertility depend on a wider context – first, family and work reconciliation possibilities that are related to social and family policy; second, the level of gender equity in individual- and family-oriented institutions. The transition from the traditional gender role model to an egalitarian gender roles model depends on the adaptability level of the institutions. As this perspective suggests, the realization of procreative intentions is limited because of the inconsistency between gender role expectations and the structures of their fulfillment possibilities. These conditions create normative confusion, a family and work reconciliation conflict. The perspective that comprises three dimensions – happiness, fertility and gender roles – is considered to be among the highly promising theoretical perspectives for analyzing the changing fertility patterns and low fertility.
Keywords: fertility; happiness; childbearing; gender roles; gender equality; gender equity